Legal Guarantees and Protection of Women's Labor Rights in the Industrial Sector: Study of IWIP Limited Company, Central Halmahera District - Madilis, Hasan; Hadi, Irfan; Ida, Nur (Journal of Law, Politic and Humanities, 2025)
This research is entitled Legal Guarantees and Protection of Women's Labor Rights in the Industrial Sector: Study of IWIP Limited Company, Central Halmahera District. This paper analyzes IWIP Limited Company, Central Halmahera District, Indonesia and aims to analyze IWIP Company’s implementation of Law Number 13 of 2003 on Labor which is the legal basis for industrial relations as well as the rights and obligations of workers, including maternity rights for female workers. This paper employed the empirical research method and was descriptive research. Results showed that in the effort to implement legal guarantees and protection of the rights of female workers according to Law Number. 13 of 2003 concerning employment, at PT. IWIP has been running well, only in several aspects regarding the Maternity Rights of female workers. in anticipating the occurrence of violence and sexual harassment in the work environment, the Guidelines for the Prevention and Handling of Sexual Violence in the Workplace will only be socialized by the Industrial Relations of PT. IWIP to determine which methods will be applied, as well as which parties are substantially related to female workers to occupy structural positions for service, supervision and action. This includes the scope of prevention and prosecution of human trafficking.